2013
DOI: 10.2298/vsp110526021s
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis in defining the optimal shape and safety factor of retentive clasp arms of removable partial denture

Abstract: The BIOS concept should be used only for RCAs made of CoCrMo alloy and different wax profiles should be used for fabricating clasps of other investigated materials. The contribution of this study may be the improve ment of present systems for defining the clasps shapes made from (CoCrMo alloys. The more significant application is the possibility of creating new concepts in defining shapes of RCA made from CPTi and polyacetale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…For better retention, less clasp taper is advised but within the acceptable aesthetics. This finding matched the previous studies conducted by Peng et al 26 and Sćepanović et al 38 The current study may have some limitations. For example, not all clasps' dimensions were tested mechanically.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For better retention, less clasp taper is advised but within the acceptable aesthetics. This finding matched the previous studies conducted by Peng et al 26 and Sćepanović et al 38 The current study may have some limitations. For example, not all clasps' dimensions were tested mechanically.…”
Section: Discussionsupporting
confidence: 92%
“…38,39 Previous studies showed higher stress values at the connection between the retentive clasp arm and the guiding plane, rendering it more prone to fracture. 1,24,26,38 Thus, keeping larger dimensions in that area is wise to endure stress concentrations. Although adequate tapering of the clasp tips is mandatory for metallic clasps because of their high rigidity, higher flexibility renders polymer clasps acceptable in less tapering values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation